Accelerated deterioration mechanism of 316L stainless steel in NaCl solution under the intermittent tribocorrosion process. (10th September 2022) - Liu, Yingrui; Liu, Linlin; Li, Shuyu; Wang, Rujia; Guo, Peng; Wang, Aiying; Ke, Peiling
Highlights: Tribocorrosion test conducted under continuous and intermittent sliding. Wear rate increased at intermittent tribocorrosion process. Repeated sliding promoted the grain refinement and regenerated passive film. Periodical removal of the solid passive film enhanced the abrasive wear. Abstract: In this research, the tribocorrosion behavior of 316L stainless steel in simulated seawater was investigated under continuous and intermittent sliding at open circuit potential. The tribocorrosion mechanism was discussed in terms of wear morphologies, mechanical property as well as chemical composition. Meanwhile, microstructure evolution inside the wear track and open circuit potential recorded after sliding were analyzed to quantify the repassivation kinetics and evaluate the impact of the regenerated passive film on wear. The results showed that the wear rate increased under intermittent sliding when the pause time is long enough to repassivate after sliding. Repeated sliding promoted the refinement of the grain inside the sliding area, which was beneficial to the generation of the thicker and more compact passive film inside the wear track. The ruptured passive film often acted as abrasives during subsequent sliding. Therefore, the accelerated material loss under intermittent sliding was attributed to the periodic mechanical removal of the thickened passive film and the enhanced abrasive wear inside the wear track.